2004
DOI: 10.1111/j.1467-8624.2004.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Social Exclusion Under Varied Conditions: Gender and Developmental Differences

Abstract: To investigate social exclusion, 146 dyads of close friends (N = 292, ages 10, 12, and 14) were observed as they played a board game with a same-gender confederate actor, trained to be a difficult play partner. Verbalizations and gestures were coded for verbal and nonverbal social exclusion, verbal aggression, and verbal assertion. The results indicated few developmental differences. For verbal responses in the presence of the actor, boys were more socially exclusive and verbally aggressive than were girls. Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 64 publications
2
41
0
2
Order By: Relevance
“…In the current study, items tapping social exclusion (e.g. being left out of everyday activities) are also included in the measure of relational victimization as prior research has suggested that social exclusion is an important aspect of relational victimization (Underwood et al, 2004). Overt victimization is measured by items tapping behaviors such as physical (e.g.…”
Section: The Current Modelmentioning
confidence: 99%
“…In the current study, items tapping social exclusion (e.g. being left out of everyday activities) are also included in the measure of relational victimization as prior research has suggested that social exclusion is an important aspect of relational victimization (Underwood et al, 2004). Overt victimization is measured by items tapping behaviors such as physical (e.g.…”
Section: The Current Modelmentioning
confidence: 99%
“…For many, this description of social exclusion parallels that of discrimination, or social rejection. Underwood et al (2004) find not only that social exclusion and social rejection are similar, but also that both create a common pathway in relationship to pain (Baumeister & Leary 1995). Indeed, it has been argued that "being excluded from social groups ranks among the most aversive of human experiences" (Labonte 2004).…”
Section: The Anterior Cingulate Cortex and Racementioning
confidence: 99%
“…Further, rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20130079 girls use more affiliative speech acts than boys, including provision of information or invitations to play. Likewise, when same-sex pairs of 10-to 14-year-old close friends played a game with a same-sex confederate who was trained to criticize, boast, boss and otherwise behave unpleasantly, girls made fewer aggressive and assertive statements than boys to the confederate [158]. Instead, girls made more subtle aggressive nonverbal facial and bodily non-contact gestures than boys.…”
Section: (I) Avoid Interference Competitionmentioning
confidence: 99%
“…Experimental investigation of 6-and 10-year-old children's responses to attaining higher in same-sex dyads showed that victorious girls exhibited more discomfort than boys after winning a game [156]. Most directly, when a same-sex confederate displayed high-status behaviours, such as boasting and bossing, compared with boys, girls rated the confederate as meaner and themselves as angrier at the confederate [158].…”
Section: (Iv) Enforce Equality Among Girlsmentioning
confidence: 99%